The Sino-American arms race in the South China Sea and future scenarios (Damascus University Journal for the economic and Political sciences, 2024)
The study aimed to identify the geographical, political and military characteristics of the South China Sea region, determine the importance of the region for both China and America, determine the reasons that push China and America to enter into an arms race in the South China Sea, and clarify the manifestations of the ongoing arms race between the two countries in the South China Sea, in addition to proposing Future scenarios for the Chinese-American arms race in the South China SeaThe study adopted the descriptive approach, the analytical approach, and the comparative approach, by defining the concepts of the arms race and describing the study area represented by the South China Sea, in addition to clarifying the factors that outperform both America and China in the arms race in the South China Sea. Armament indicators for both America and China were also determined. In the South China Sea, the study suggested three scenarios for the Sino-American arms race in the region. The first is based on the intensity of the arms race remaining as it is now without one party gaining dominance over another, while the second is based on China’s superiority and the decline of the American role in armaments in the region. As for the scenario The third is based on the superiority of the United States in this race.
Keywords: Arms race; China; America; South China Sea